Pengaruh Post Weld Heat TreatmentTerhadap Sifat Mekanis dan Korosi Sambungan Las Spiral Saw pada Pipa Baja ASTM A252 - Ipick Setiawan; Mochammad Noer Ilman (Department of Mechanical Engineering, University of Udayana, 2012)
Metal joint with welding system is increasingly used. i.e structure, piping or machine constuction. Some ofthe problems on welding is residual stress dan over hardness can decrease the weld toughness stresscorrosion cracking. An effort to solve this problem is PWHT. PWHT has multiple functions, those are toreduces residual stress,increases ductility of HAZ and improves toughness in weld metal and HAZregions.Heating process with various temperature is expected to make optimum PWHT temperature.Thisexperiment was carried out to know the effect of PWHT torwad the toughness an corrosion of helicalwelding pipe ASTM A252. The welding process use SAW with groove double V, electrical current 375 A ,voltage 35 V and heat input 2,8 kj/mm. Post weld heat treatment was carried out at various temperature450oC, 550oC and 650oC during 3 hours followed by cooling process in furnace after that, these specimensware tested the hardness, tensile strength, toughness and corrosion. The Result of research show thatincreasing of PWHT temperature, can increase the toughness and corrosion resistance of joint weldin, butthe tensile strength is decreasre. The optimum PWHT temperature is 550o C with toughness 81 J at 0O C.